Implementation of Good Governance in the Cost of Education Functions through Government Scholarships - Kumba Digdowiseiso; Ifan Firmansyah; Andi Nurcahya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Education services are the leading sector in accelerating the rate of human growth and the human development index (HDI) by applying three principles of good governance, namely participation, transparency and effectiveness and efficiency. The purpose of this study is to examine the implementation of good governance in the cost of the education function through educational scholarships. This research uses a literature study method by collecting library data, reading, taking notes and managing writing materials. The results of the study show that the government has succeeded in implementing the principles of good governance which include participation, transparency and effectiveness and efficiency in the education sector. The principle of participation is shown in the increase in the human growth index every year. Then the principle of transparency is aimed at ease of access to obtain educational information from the government for the community. Furthermore, the government in the principle of being effective and efficient has implemented the scholarship assistance program on target. So that the implementation of good governance by the government in spending on education functions through educational scholarships has been carried out properly.